Black Graduate Students’ Social Relationships with White Professors and Students in a Predominantly White Public University - Juanita Johnson-Bailey; Thomas Valentine; Ronald M. Cervero (Adult Education Research Conference, 2008)
This study employs a mixed method approach to understanding the cross-racial relationships experienced by Black graduate students at a major Southern research university. Data were collected using a multifaceted mailed survey. Cluster analysis was employed to construct a four-part typology of cross-racial social relationships. Qualitative comments were examined to better understand the identified types. The study reveals the variety of perceived social relationships experienced within a single university.